Análise de viabilidade econômico financeira para a implantação de um studio de pilates - Oliveira, Fábia Elizabeti Diniz de (Universidade Federal Rural do Semi-Árido, 2018)
The tertiary sector of the economy has presented growth results in the last years, as a result of the increase of entrepreneurs in several branches, for example, in the health care sector, where people seek to improve the quality of life. Through this aspect, the main objective of the present study was to apply the tools for analysis of financial economic viability for the implementation of a Pilates Studio in the city of Governador Dix-Sept Rosado in Rio Grande do Norte. For this purpose, a questionnaire was designed to identify demand and consumption seasonality, where it was possible to predict demand and design cash flow. Based on this cash flow, it was possible to calculate and analyze the main financial indicators necessary to assist in decision making regarding the opening of the enterprise, such as Net Present Value (NPV), Internal Rate of Return (IRR), Payback and elaboration of the sensitivity analysis of gross revenue in relation to NPV. After the analysis, the indicators found were positive, which makes the execution of the project feasible.
Monografia
Keywords: Viabilidade; Pilates; Studio; Implantação; Viability; Pilates; Studio; Implantation; ENGENHARIAS::ENGENHARIA DE PRODUCAO